Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Pelanggan pad PT Gunung Kawi - hendry; Winda Evyanto, S.S., M.MPd. (LPPM Universitas Putera Batam, 2022)
In the era of today's level of business competition, we can even say that every company is trying to survive in the business world.This study aims to determine the effect of service quality and promotion on customer satisfaction at PT Gunung Kawi. PT Gunung Kawi is a company engaged in distributors located in Batam, Riau Islands. The tool used in this study is multiple linear regression analysis with a total of 129 respondents and using SPSS as a tool in managing the data obtained. The results of this study are the Service Quality variable (X1) has a positive and significant effect on Customer Satisfaction (Y), and the Promotion variable (X2) has a significant influence on Customer Satisfaction (Y) and the Service Quality variable (X1) and Promotion (X2) has a significant impact. simultaneously has a positive and significant impact on customer satisfaction (Y) at PT Gunung Kawi in batam city.